THE DEVELOPMENT DYNAMIC OF HIV/AIDS IN LAMPUNG USING NONLINEAR DIFFERENTIAL EQUATION MODEL OF SIR (SUSCEPTIBLE, INFECTIOUS, AND RECOVERED) - Dorrah Azis; Agus Sutrisno; Ruby T; Handoko (Journal of Innovation Research and Knowledge, 2024)
This study discusses the dynamics of the development of HIV/AIDS in Lampung using SIR nonlinear differential equation model. The data is used on the number of people of HIV/AIDS and the number of residents in Lampung in 2016-2017 from the Central Bureau of Statistics and Ministry of Health Republic of Indonesia Diseases Prevention Directorate. Stability analysis results based on the eigen values of the Jacobian matrix obtained disease free equilibrium point is that are semi stable due to the threshold phenomenon with eigen values and . The basic reproductive number of HIV/AIDS in Lampung at 90,313. These results indicate the HIV/AIDS epidemic will cause within a period of up to 100 years into the future.